Can Grace Be Streamed? The Roman Catholic Liturgy and the Crisis of Embodiment - Immanuel, Leena (2025)
The COVID-19 pandemic precipitated a dramatic shift in the liturgical life of the Roman Catholic Church, as worship moved from physical gatherings to digital platforms. This article critically examines the theological and pastoral implications of this digital turn, particularly in light of the Church's longstanding emphasis on embodiment as essential to sacramental worship. Drawing from sacramental theology, ecclesiology, and contemporary liturgical scholarship, the paper explores the tensions between digital mediation and the incarnational logic that undergirds Catholic liturgy. While digital worship served as a vital pastoral bridge during the crisis, it also exposed deep questions about presence, participation, and grace. The article argues for a renewed theological engagement with embodiment—not as a return to pre-pandemic norms, but as a necessary re-imagining that responds faithfully to evolving cultural and technological realities. In doing so, it seeks to offer a constructive path forward for liturgical practice that is both rooted in tradition and contextually aware.
Keywords: digital liturgy; virtual sacraments; online worship; Digital church; Sacramental Theology